Pengembangan Komik Digital Subtema Binatang di Hutan terhadap kemampuan berhitung Anak Usia Dini - Reswita; Wahyuni, Sri (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
The problem in this study is how the procedure for developing comic strips with animal subthemes in the forest as a medium to instill character for children aged 5-6 years. This research aims to develop comic subthemes of animals in the forest for the numeracy ability of children aged 4-6 years. This study uses the type of Research and Development (RnD) research based on the Borg and Gall research model procedure modified by Sugiyono consisting of 10 steps, but the researcher only uses 7 steps, namely potential and problem, data collection, product design, design validation, product revision, trial, and product revision. The comic product of the animal subtheme in the forest was validated by 2 experts, namely material experts and media experts. From the two experts, they received a validation score of 89.73% which received a very valid category. This comic was field tested on eight children aged 5-6 years. The trial is divided into 2, namely individual trials and group trials. From the results of the field trial, a feasibility score of 91.7% and 80.55% was obtained in the feasible category. The implications of this research indicate that the forest animal-themed comic is effective as a medium for instilling character in children aged 5-6 years, as well as having the potential to improve their counting skills. With high feasibility scores from the field trials, the use of this comic can be integrated as an alternative, engaging, and educational learning tool in kindergartens, particularly for the development of children's cognitive and character aspects.